2019
DOI: 10.1038/s41467-019-12412-1
|View full text |Cite
|
Sign up to set email alerts
|

Fate-mapping post-hypoxic tumor cells reveals a ROS-resistant phenotype that promotes metastasis

Abstract: Hypoxia is known to be detrimental in cancer and contributes to its development. In this work, we present an approach to fate-map hypoxic cells in vivo in order to determine their cellular response to physiological O2 gradients as well as to quantify their contribution to metastatic spread. We demonstrate the ability of the system to fate-map hypoxic cells in 2D, and in 3D spheroids and organoids. We identify distinct gene expression patterns in cells that experienced intratumoral hypoxia in vivo compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
157
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(166 citation statements)
references
References 75 publications
9
157
0
Order By: Relevance
“…Additionally, ROS produced by sublethal levels of antibiotics induces antibiotic resistance, but ROS triggered by lethal levels of antibiotics promotes bacterial killing and suppresses resistance (Van Acker & Coenye, 2017; Zhao, Hong, & Drlica, 2014). As a critical factor affecting several cancer hallmarks, ROS is also involved in the acquisition of self‐sufficiency in proliferation signals by a ligand‐independent receptor tyrosine kinase transactivation as well as the loss of contact inhibition and anchorage‐dependence cell growth (Godet et al, 2019; Ishikawa et al, 2008; Poillet‐Perez, Despouy, Delage‐Mourroux, & Boyer‐Guittaut, 2015; Wang, Hou, Su, Zhao, & Shi, 2017). Moreover, ROS can affect many signaling pathways, including mitogen‐activated protein kinases signaling pathways (MAPK) (Avisetti, Babu, & Kalivendi, 2014; Shen & Liu, 2006; Zibara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ROS produced by sublethal levels of antibiotics induces antibiotic resistance, but ROS triggered by lethal levels of antibiotics promotes bacterial killing and suppresses resistance (Van Acker & Coenye, 2017; Zhao, Hong, & Drlica, 2014). As a critical factor affecting several cancer hallmarks, ROS is also involved in the acquisition of self‐sufficiency in proliferation signals by a ligand‐independent receptor tyrosine kinase transactivation as well as the loss of contact inhibition and anchorage‐dependence cell growth (Godet et al, 2019; Ishikawa et al, 2008; Poillet‐Perez, Despouy, Delage‐Mourroux, & Boyer‐Guittaut, 2015; Wang, Hou, Su, Zhao, & Shi, 2017). Moreover, ROS can affect many signaling pathways, including mitogen‐activated protein kinases signaling pathways (MAPK) (Avisetti, Babu, & Kalivendi, 2014; Shen & Liu, 2006; Zibara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because the MARCer construct is constitutively expressed, short episodes of hypoxia could induce labelling, but this may not be seen in proximity to EF5 due to re-oxygenation between the time tamoxifen was given and injection of EF5. Other research has also shown that hypoxic cells move out of hypoxic EF5 + or pimonidazole + areas (Harada et al, 2012;Erapaneedi et al, 2016;Conway et al, 2018;Godet et al, 2019) followed by random distribution. The transient nature of the hypoxic state may explain that the induction of tdTomato expression does not correlate with the level of acute hypoxia 2, 5, 9, 16, 21 days later.…”
Section: Discussionmentioning
confidence: 92%
“…This is likely due to the requirement of O2 for GFP folding and fluorescence (Heim et al, 1994;Kumagai et al, 2013), making it a suboptimal fluorescent marker to track current hypoxia. On the other hand, Godet et al were able to visualise GFP under 0.5% O2 (Godet et al, 2019). Also, processing of the samples exposes them to atmospheric oxygen, possibly introducing enough oxygen for GFP maturation ex vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations